Pulmonary Contusion Similar to COVID-19 Pneumonia - Seung Hwan Lee; Sung Youl Hyun; Yang Bin Jeon; Jung Nam Lee; Gil Jae Lee (Journal of Trauma and Injury)
The Coronavirus disease 2019 (COVID-19) has rapidly spread across the world and caused a pandemic. It can be transmitted by an infected person or an asymptomatic carrier and is a highly contagious disease. Prevention and early identification of COVID-19 are important to minimize the transmission of COVID-19. Chest computed tomography (CT) has a high sensitivity for detecting COVID-19, but relatively low specificity. Therefore, chest CT may be difficult to distinguish COVID-19 findings from those of other infectious (notably viral types of pneumonia) or noninfectious disease. Pulmonary contusion has also a lot of similarities on chest CT with COVID-19 pneumonia. We present trauma patients with pulmonary contusion whose CT scans showed findings similar to those of COVID-19, and we report our experience in the management of trauma patients during the COVID-19 pandemic.